Isolation of Endophytic Bacteria from Palm Oil Fruits and Characterization of Their Lipases - FANDY DJAFAR; TRESNAWATI PURWADARIA; ARNOLD PARLINDUNGAN SINURAT (Indonesian Society for microbiology, 2010)
Lipases (EC 3.1.1.3) can be produced in palm oil fruits by fruit cells or endophytic microbes. The purpose of this research is to isolate endophytic lipolytic bacteria of palm oil fruit and characterization their lipases. The bacteria were isolated and screened using medium Kouker and Jaeger containing olive oil, minerals, yeast extract, peptone, agar, and rhodamine B as an indicator. Fifteen endophytic bacteria were isolated and identified having the microbial lipase activity. Most of them showed rod shape, positively Gram test, spore formation, and motility except one bacteria strain K which was coccus. The enzyme was produced using submerged culture in the same medium but not containing agar and rhodamine B. Based on data of enzyme activity towards p-nitrophenyl palmitate as a substrate, protein concentration, and specific activity, two bacteria were selected, those were BSWt2(1) and Ink 1.3 isolates. Microscopic and biochemistry analyses show that BSWt2(1) and Ink 1.3 were identified as Bacillus brevis and B. lacterosporus respectively. Crude lipase from B. brevis BSWt2(1) and B. lacterosporus Ink 1.3 showed optimum activities at pH 8.0-9.0 and 60°C, and at pH 8.5 and 60-70°C. The enzymes were stable pre-incubated at pH 7.5-9.0 and pH 7.5-8.0 respectively, and they were stable pre-incubated for 2-4 hours at 80°C and for 2-8 hours at 100°C. Based on stability in high temperature, lipase from both isolates were specific and might be applicable for use in waste water treatment in palm oil factories.